From Policy-Practice to Means-Ends Decoupling in Organizations: A Systematic Review and Paths for Future Research - Jabbouri, Rachid; Schneckenberg, Dirk; Truong, Yann (Management international / International Management / Gestiòn Internacional, 2022)
Recent developments in the innovation literature suggest that even when an organization truthfully implements the adopted R&D policy, it may still fail to achieve its intended goals, a phenomenon called means-ends decoupling. We employ a systematic literature review to answer the question of “what is the current state of knowledge in the phenomenon of means-ends decoupling in the literature” and “where it can move in the future.” Our paper provides a framework that delineates means-ends decoupling from policy-practice decoupling and identifies the underlying mechanisms that explain when and how means-ends decoupling may occur within an organization’s activities.